2009
DOI: 10.1080/18811248.2007.9711557
|View full text |Cite
|
Sign up to set email alerts
|

JENDL Actinoid File 2008

Abstract: JENDL Actinoid File 2008 (JENDL/AC-2008) was released in March 2008. It includes nuclear data for neutron-induced reactions for 79 nuclides from Ac (Z ¼ 89) to Fm (Z ¼ 100). The neutron energy range is 10 À5 eV to 20 MeV. Almost all data for 62 actinoids in JENDL-3.3 were revised. New evaluations were performed for 17 nuclides, which have half-lives longer than one day. A new comprehensive theoretical model code CCONE was widely used for the evaluation of cross sections and neutron emission spectra. Thermal cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Matsuoka and Ito [9] have shown that the application of a JENDL Actinide file 2008 [18] as the nuclear data library of MVP-BURN to the isotopic composition analysis of BWR MOX fuel samples of about 75 to 80 GWd/t in the MALIBU program gives about 2% to 10% overestimates of the measured isotopic compositions of 238 Pu while applying JENDL-3.3 shows about 5% to 10% underestimates though they are not shown in Figure 3. The burnup calculations of MVP-BURN for both libraries were performed by using the general-purpose chain model (u4cm6fp104bp12T).…”
Section: Introductionmentioning
confidence: 87%
“…Matsuoka and Ito [9] have shown that the application of a JENDL Actinide file 2008 [18] as the nuclear data library of MVP-BURN to the isotopic composition analysis of BWR MOX fuel samples of about 75 to 80 GWd/t in the MALIBU program gives about 2% to 10% overestimates of the measured isotopic compositions of 238 Pu while applying JENDL-3.3 shows about 5% to 10% underestimates though they are not shown in Figure 3. The burnup calculations of MVP-BURN for both libraries were performed by using the general-purpose chain model (u4cm6fp104bp12T).…”
Section: Introductionmentioning
confidence: 87%
“…• JENDL/AC-2008 [11] (Japan, 2008) for transmutation study, • EAF-2010 [12] (UK, 2010) for activation and transmutation studies, • FENDL-2.1 [13] (IAEA, 2004) for fusion applications, and • IRDFF-1.0 [14] (IAEA, 2012) for dosimetry applications.…”
Section: Evaluated Nuclear Data Libraries Available In the Worldmentioning
confidence: 99%
“…The nuclear data of 156 materials were selected from mainly ENDF/B-VII.0 and partly JENDL/AC 22) and IAEA NDS project.…”
Section: Matxs File In Ads-20mentioning
confidence: 99%